Determinants of Utility Perception of Telecasted Agricultural Technologies - R.T. Katole; D.D Suradkar; R.S. Bhople (Journal of Agricultural Extension Management, 2025)
The present agricultural strategy in India calls for speedy dissemination of agricultural information and technical knowledge to the farming community. Mass media are important carriers of information in a modern developing and developed society. Media are important contributors to the ongoing technological changes. Television happens to be the most useful media of modern times. Realizing its importance a countrywide network of television was established in the country to spread information to a large section of population at a high speed. Agriculture being an important sector of the Indian economy, agricultural information is being disseminated through television under its agricultural programme. The value of any programme can only be judged through audience response. Dale (1963) opined that an agricultural expert could influence more farmers by a 10 minutes television demonstration than a week’s travel. This emphasizes the role of television in dissemination of agricultural technology. Studies have been undertaken in the past on assessing of effectiveness of agricultural telecast programme on the farming community. In the present study, an attempt has been made to assess the perceived usefulness of selected agricultural technologies telecast through an agricultural programme, "Amchi Mati Amchi Mansa" by the farmers, by developing standardized scales.